Islamic Parenting Model to Increase Family Literacy: A Mixed Method Study - Purwandari, Septiyati; Husna, Aftina Nurul; Tawil, Tawil (Universitas Muhammadiyah Yogyakarta, 2022)
Low literacy within Muslim families can seriously affect developing individuals and society. This study aims to test the effectiveness of a new model of Islamic parenting based on family religiousness to address the low literacy issue in Muslim families. Using a mixed-method with triangulation design, in Study 1, researchers conducted action research by delivering a six-session parent training program to 10 women with children aged 11 years old, grouped into high and low-literate families. Practice at home, guided by facilitators, followed each session. Data were collected using interviews and parents’ reflection journals and were analyzed using content analysis. In Study 2, concurrently with Study 1, a quasi-experimental research was conducted using a one-group pre-test and post-test design to test the model’s effectiveness. Before and after the programs, the researchers administered the Family Literacy Questionnaire to the women and the Literacy Activity Questionnaire to their children. The data were analyzed using the Wilcoxon signed-rank test to examine differences between pre-test and post-test scores. The program was perceived as impactful and highly appreciated by the participants, who expected its continuation in the future. The hypothesis test results indicated that the Islamic parenting model improved family literacy (p=0.043) and the literacy activities of their children (p=0.039). The Islamic parenting model effectively enhanced women’s family literacy in low literacy groups and children’s literacy activity in both groups. This finding can be widely implemented to provide parents with understanding and skills to support their children’s literacy.